Job Burnout as a Predictor of Teachers’ Level of Life Satisfaction During the COVID-19 Pandemic - Özpolat, Ahmet Ragıp; Bahar, Hüseyin Hüsnü; Aslıyüksek, Zekiye Şeyma (Technium Social Sciences Journal, 2025)
After the outbreak of the COVID-19 virus, almost all employees have experienced changes to their working conditions. Concepts such as distance work, distance education, and online teaching have been encountered by teachers, the instructional techniques have changed and the use of technology has become more prevalent. Due to the changes in teaching roles during distance education practices, re-examining teachers’ life satisfaction levels has been considered to be necessary. Totally 535 teachers working in both public and private schools in Istanbul were contacted in order to examine the role of job burnout in predicting life satisfaction among teachers during the COVID-19 pandemic. Maslach Burnout Inventory-Educators Survey (MBI-ES) and Satisfaction with Life Scale were used as data collection tools in the study. The theoretical model tested within the scope of the study was verified. According to the verified model, job burnout of teachers during the COVID-19 pandemic was found to be a negative and significant predictor of life satisfaction. The findings were discussed in line with the literature. Recommendations were made to increase the motivation of teachers.